Equalizing Quality: The Challenge of Globalization - Savira, Siti Ina (Universitas Negeri Surabaya, 2015)
This essay is aimed to discuss one contemporary issue in relation to Indonesia. The issue being raised here is globalization and its effect on how Indonesia perceived itself as a nation. This paper will argue my position in viewing globalization as a force that seems to manifest in a blind movement that rapidly change our way of life at the cost of social justice. One example I emphasize on my paper is the impact in educational paradigm, which can be seen from some educational discourses.